Pedagogical Management of Educational Process of Gifted Children - Taran R. I. (Psychological and Pedagogical Support of Talented Children: Problems, Directions, Approaches, Conditions, 2020)
the Belarusian work experience of the teaching staff with gifted children is presented in the article. This teaching staff was led by the author of the article in the 1990s. Research in the field of psychology shows that children with high educational abilities make up 15–20%. They are distinguished by tireless curiosity, the desire to constantly load themselves with cognitive and search tasks, etc. The target function of the national education system of Belarus is to create conditions for the development of talents, personal abilities and their use for the benefit of society and themselves.
Keywords: одаренные дети; gifted children; одаренные; педагогическое руководство; gifted; pedagogical managment